2013
DOI: 10.5194/amt-6-2239-2013
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of OMI ozone profile retrievals in the upper troposphere and lower stratosphere by the use of a tropopause-based ozone profile climatology

Abstract: Motivated by the need of obtaining a more accurate global ozone distribution in the upper troposphere and lower stratosphere (UTLS), we have investigated the use of a tropopause-based (TB) ozone climatology in ozone profile retrieval from the Ozone Monitoring Instrument (OMI). Due to the limited vertical ozone information in the UTLS region from OMI backscattered ultraviolet radiances, better climatological a priori information is important for improving ozone profile retrievals. We present the new TB climatol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 37 publications
1
50
0
Order By: Relevance
“…In subsequent validation studies, good agreement was found between OMI SOE ozone profiles and high resolution ozone profiles made by satellite and ozonesonde (Liu et al, 2010b;Wang et al, 2011). The SOE algorithm was shown to capture very well the ozone variability in the extratropical tropopause region through comparison with aircraft and ozonesonde measurements (Pittman et al, 2009;Bak et al, 2013).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In subsequent validation studies, good agreement was found between OMI SOE ozone profiles and high resolution ozone profiles made by satellite and ozonesonde (Liu et al, 2010b;Wang et al, 2011). The SOE algorithm was shown to capture very well the ozone variability in the extratropical tropopause region through comparison with aircraft and ozonesonde measurements (Pittman et al, 2009;Bak et al, 2013).…”
Section: Introductionmentioning
confidence: 85%
“…TOMS mean biases range from −2.1 % to −1.3 % and SOE mean biases are less than ± 0.4 % over all the given bins except at the lowest total ozone value where the mean bias is ∼ 1 %. Use of the improved tropopause-based ozone profile climatology presented by Bak et al (2013) in the SOE algorithm further reduces the total ozone dependence slightly in both mean biases at low ozone amounts and standard deviations at high ozone amounts (see the red dashed line in Fig. 5e).…”
Section: Total Ozone Column Dependencementioning
confidence: 99%
“…Vertically, the SD typically maximizes in the upper troposphere and lower stratosphere (UTLS) in all latitude bands due to significant ozone variability and a priori uncertainty. Bak et al (2013b) showed that the use of tropopause-based (TB) ozone profile climatology with NCEP Global Forecast System (GFS) daily tropopause pressure can significantly improve the a priori and eventually reduce the retrieval uncertainty. Consequently, the SDs of OMI-sonde differences in the UTLS at middle and high latitudes can be reduced through reducing the retrieval uncertainties in a future version of the algorithm that uses the TB climatology.…”
Section: Comparison Methodologymentioning
confidence: 99%
“…The a priori data for ozone are one of the key optimal estimation inputs, because the retrieval so-lution comes mainly from a priori information rather than measurement information where the instrument sensitivity to the true ozone profile is insufficient. The a priori value (X a ) and a priori error covariance (S a ) of ozone is taken from the tropopause-based ozone profile climatology that is optimized to represent the dynamical ozone variability in the upper troposphere and lower stratosphere (Bak et al, 2013b). The measurement vector Y is defined as the logarithm of the earthshine radiances normalized to the daily solar irradiance.…”
Section: Omps Ozone Profile Retrievalsmentioning
confidence: 99%
“…Its successors continued the role of GOME for atmospheric ozone monitoring with SCanning Imaging Absorption SpectroMeter for Atmospheric CHartographY (SCIAMACHY; Bovensmann et al, 1999) aboard the Environmental Satellite (ENVISAT), GOME-2s (EUMETSAT, 2006) aboard the MetOp-A and MetOp-B and Ozone Monitoring Instrument (OMI; Levelt et al, 2006) flown on the EOS Aura spacecraft. The high performance of OMI ozone profile retrievals in both stratosphere and troposphere has been demonstrated through extensive validation efforts using ozonesondes, aircraft, satellite data and ground-based total ozone data (Pittman et al, 2009;Liu et al, 2010;Bak et al, 2013bBak et al, , 2015Huang et al, 2017a, b). However, a portion of OMI radiance measurements has been affected by the partial blockage of the instrument's entrance slit, a problem termed the row anomaly, which started in 2007 and grew serious in January 2009 (Schenkeveld, 2017).…”
Section: Introductionmentioning
confidence: 99%